Le mausolée turriforme d’une villa près de Carcassonne/Carcasso (Aude) - Richard Pellé (Gallia)
In the last decades of the 1st c. BC, around the time when Carcassonne acquired the title of city under Latin law, Montredon hill, located near the city and the via Aquitania, and occupied since the Neolithic, was completely transformed by the creation of a large rural villa-type area. The design of the residential part, pars urbana, follows a classic plan reminiscent of the major villae of Lazio. It is centred on the atrium and its colonnade peristyle, with a southern facade opening towards the south on a vast space surrounded by walls, interpreted as a "private park". In this "park", the monumental tomb of one of the first owners of the villa, if not the founder, was erected. This mausoleum is in all respects remarkable. Owing to its chronology, it constitutes a category of monument with an underground funeral chamber, which seems to be rare in Gaul or in the western part of the Empire and remains exceptional for this important time of the change of era.